Прийняття рішень в многоагентних системах - Овчаренко, Є. С. (ХНУРЕ, 2020)
In systems, he applies the idea of formal mathematical modeling (description) of the behavior of elements, similar to how this is done for technical control objects. This is the basis of the mathematical apparatus of game theory and the well-known mathematical decision-making models. The game theory apparatus is being developed taking into account the needs of the management tasks being solved. Therefore, it is necessary to propose models and decision-making methods that show how to build models of organizational and socio-economic systems in the form of multi-agent systems.
Keywords: багатоагентна система; мультиагентний підхід; ІВМ